2012
DOI: 10.1037/a0027639
|View full text |Cite
|
Sign up to set email alerts
|

Role of identity integration on the relationship between perceived racial discrimination and psychological adjustment of multiracial people.

Abstract: This study examined relations between perceived racial discrimination, multiracial identity integration (i.e., racial distance and racial conflict), and psychological adjustment (i.e., distress symptoms, positive affect, and negative affect) of 263 multiracial adults, using an online cross-sectional survey design. As hypothesized, higher levels of perceived racial discrimination was related to lower levels of psychological adjustment (i.e., higher distress symptoms and negative affect). Also, higher levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
117
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(126 citation statements)
references
References 61 publications
7
117
2
Order By: Relevance
“…This is inconsistent with the literature that suggests experiences of getting questioned, stared at, or wrongly classified by others due to having an ambiguous racial appearance are significant risk factors (Gaskins, 1999; Jackson et al, 2012). It is possible that perceived racial ambiguity is correlated with more chronic and stable measures of psychological adjustment, rather than our more situational-based measures of psychological adjustment (i.e., DASS-21 measured distress in the past week.…”
Section: Summary and General Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…This is inconsistent with the literature that suggests experiences of getting questioned, stared at, or wrongly classified by others due to having an ambiguous racial appearance are significant risk factors (Gaskins, 1999; Jackson et al, 2012). It is possible that perceived racial ambiguity is correlated with more chronic and stable measures of psychological adjustment, rather than our more situational-based measures of psychological adjustment (i.e., DASS-21 measured distress in the past week.…”
Section: Summary and General Discussioncontrasting
confidence: 73%
“…We anticipated that racially color-blind individuals who are unaware of and in denial of racism (Neville, Lilly, Duran, Lee, & Browne, 2000) are less likely to be attuned to uniquely racialized threats and develop appropriate coping responses. We also expected a significant positive correlation between identified risks of multiracial experiences and perceived conflict and distance of individuals' multiple racial identities, while a significant negative correlation between identified resilience of multiracial experiences and perceived conflict and distance of individuals' multiple racial identities (Jackson et al, 2012). Finally, we expected identified risks of multiracial experiences would be negatively correlated with emotional well-being (i.e., negatively correlated with positive affect, and positively correlated with negative affect).…”
Section: Studymentioning
confidence: 95%
See 1 more Smart Citation
“…In the only prior work to examine perceived discrimination and well-being among multiracial people, Jackson et al (2012) similarly found that perceived discrimination was linked to psychological distress. Thus, like for other minority groups (Pascoe & Richman, 2009), perceived discrimination appears to be a threat to well-being.…”
Section: Discussionmentioning
confidence: 88%
“…Presently, only one published study has quantitatively examined the relationship between multiracial people's perceptions of discrimination and their psychological well-being. Jackson, Yoo, Harrington, and Guevarra (2012) found that multiracial participants' self-reports of discrimination were positively correlated with psychological distress and negative affect. In the present research, we again examine the relationship between multiracial people's perceptions of discrimination and well-being.…”
mentioning
confidence: 96%